On the theory and computation of anisotropie damage at large strains - Menzel, Andreas; Steinmann, Paul (European Journal of Computational Mechanics, 2001)
The goal of this contribution is the formulation and algorithmic treatment of anisotropie continuum damage mechanics at large strains. Based on the concept of an isotropie, fictitious and undamaged configuration a Finger-type damage metric tensor in terms of the fictitious linear tangent map is introduced. Referring to the principle of strain energy equivalence with respect to the fictitious, effective space and the standard reference configuration the free Helmholtz energy can be formulated within the standard reference configuration and treated in the spirit of standard dissipative mate rials. Thereby, the introduced damage potential substantially affects the anisotropie nature of the damage formulation. Final/y, sorne numerical examples demonstrate the applicability of the proposed framework.